Attitudes and driving factors behind the attitudes of Malaysian university students towards English and American English - Wan Shamsuddin, Wan Noor Farah; Abdullah, Ain Nadzimah; Tan, Helen; Bolong, Jusang (Global Academic Excellence, 2019)
This article explores the attitudes of 340 Malaysian students in a public university in Klang Valley towards two main English varieties in Malaysia: i) British English and ii) American English. Data were acquired by employing the Verbal Guise Technique (VGT) to determine the participants’ covert attitudes towards the two varieties. Some attitudinal questions were also used to obtain participants’ composite attitudes towards British English and American English. To further probe into the driving factors behind the attitudes, an interview was carried out with the participants. This study found that Malaysian undergraduate students prefer American speakers over British speakers. The participants also associated American speakers as ‘easier to understand’, ‘clear’, and ‘similar to Malaysian English’. This study also found that the strong influence of British English in the Malaysian education system and the influence of media both impacted attitudes and perceptions towards the two English varieties.